ROMANTIC HUMAN STUDY: PECULIARITIES OF PERSONALITY PHILOSOPHY IN THE LITERATURE OF THE 1820-1830-IES. - T. N. Zhuzhgina-Allahverdian; S. A. Ostapenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of the study is to show the connection of romanticism with the anthropological doctrine that goes back to Hegelianism and Kantianism, and at the same time – with the concepts of the future, structuralism and postmodernism. Theoretical basis. The man is a central figure of the Romantic literary, therefore it makes sense to single out romantic human anthropological doctrine and the image of man associated with a specific historical and cultural era called the "epoch of romanticism"; to show that many romantic philosophical positions remained relevant to the basic foundations of contemporary anthropological research and coincide with it in analytical and critical thinking about a man, a person, his historical and evolutionary fate. Originality. The romantic worldview determined the specifics of anthropological discourse, both logical and illogical, remaining symbols and attaching, as for example, a real historical anecdote, a popular history, a philosophical thought, a myth, a famous literary episode and the arts multiplied by creative inspiration and imagination. This tendency determined the fragmentation of thinking and the scientific image of man as a dual being, nevertheless, presented and described in all the variety of relations with the world and with himself, that allows us to call this area of thought "the romantic human science". Conclusions. Structural analysis of numerous romantic texts allows us to draw the following conclusion: with mythopoetic imagery and anthropological thought about a man, romantic writers introduced the reader to any wisdom, to philosophical understanding of their human essence, to past and modern teachings, in a way processed antique, medieval and enlightening views, in which an important place was given to reflections on the place of man in nature, society, and history. Correlating the well-known statements about a person as a descendant of the "old Adam", "person", "personality", "soul", with the modern idea of historical and social development, about the evolution of the consciousness of a person who revealed himself as an individual in modern times, with scientific and aesthetic views, the writers of the first half of the XIX century gave romantic thought anthropological meaning and, in fact, laid the foundations of historical, social, psychological, cultural and psychoanalytic anthropology.